Development of Proficiency Testing Provider in Urine Pregnancy Testing, Urine Glucose and Urine Protein Testing of Primary Care Unites - เนตรเรืองแสง วันวิสาข์; ไพโรจน์ ธัญญลักษณ์; โพธิพิทัก ทิพย์รัตน์ (Journal of Health Science of Thailand, 2024)
This study aimed to enhance the proficiency testing program for urine pregnancy, glucose, and protein testing in primary care units. We developed processes for sample preparation, document delivery, and participant communication. The proficiency testing provider (PTP) improved sample preparation, ensuring homogeneity and stability in PT samples for urine pregnancy, glucose and protein testings throughout the reporting period. Document delivery transitioned from postal to electronic resulting in the reduction of expenses by 56.1% and paper usage by 80.0%. Improved participant communication increased the reporting rate from 81.3% to 98.4%. It has been a 5-year PT program from 2019 t0 2023, resulting in a reduction of expenses by 56,879 baht (35.43%). The analytical aspect of the PT program contributed to the development of both the PTP and participant advantages. Ultimately, the PT program results for primary care units could offer a policy proposal for organizations to oversee the quality of primary care unit laboratories.